2020
DOI: 10.1080/13685538.2020.1769589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microsurgical varicocele repair on sexual functions and testosterone in hypogonadal infertile men with varicocele

Abstract: Objective: To investigate effect of microsurgical varicocele repair on sexual functions and serum total testosterone level in infertile hypogonadal men with varicocele, and also to determine factors that might predict improvement in total testosterone level after surgery. Methods: The study included 202 infertile hypogonadal men (total testosterone level of <3.5 ng/mL) with varicocele who underwent microsurgical sub-inguinal varicocele repair. Results: Mean serum total testosterone level significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Mean serum TT levels increased from 255 ± 66 ng/dL to 372 ± 134 ng/dL (p = 0.000), while serum FSH (p=0.198), LH (p=0.207) and prolactin (p=0.345) levels did not significantly change from pre to post-operative period. Also, IIEF-EF score significantly increased from 27.47 ± 2.96 (15–30) to 28.61 ± 2.02 (18–30), after surgery (p=0.000) ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean serum TT levels increased from 255 ± 66 ng/dL to 372 ± 134 ng/dL (p = 0.000), while serum FSH (p=0.198), LH (p=0.207) and prolactin (p=0.345) levels did not significantly change from pre to post-operative period. Also, IIEF-EF score significantly increased from 27.47 ± 2.96 (15–30) to 28.61 ± 2.02 (18–30), after surgery (p=0.000) ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, some trials demonstrated the improvement in seminal parameters such as motility, sperm concentration and Total Motile Sperm Count (TMSC) ( 20 , 31 ) after correction of varicocele. The benefit related to improvement of FSH and LH levels remains uncertain ( 18 , 19 , 21 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, recent trials support the correlation between varicocelectomy and improved seminal parameters [25]. Since appropriate intratesticular testosterone levels are necessary to guarantee spermatogenesis, the investigation of Lyedig cell function is fundamental to the evaluation of infertile patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Saylam et al demonstrated that mean serum total testosterone level significantly increased from 2.55 to 3.72 after varicocelectomy (p < 0.0001), and 105 patients (52%) had a serum total testosterone level of ≥ 3.5 ng/mL after the surgery [25].…”
Section: Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation